2018
DOI: 10.1109/tpc.2018.2795398
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Personal Conceptions of Usability and User Experience of Electronic and Software Products

Abstract: Research problem: Despite the abundance of research into usability and user experience (UX), there is still debate about the relationship between both concepts. The user perspective is underrepresented in all discussions. This study examines the personal conceptions that users of electronic and software products have of usability and UX. Research questions: 1. How do users of electronic and software products conceptualize usability and UX? 2. What do they think is the relationship between both concepts? Litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Findings were considered as usability problems if they affected the five components of usability [23], i.e., learnability, efficiency, memorability, errors and satisfaction. It is important to consider usability as it would show how an interface could support its users in achieving their goals [24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Findings were considered as usability problems if they affected the five components of usability [23], i.e., learnability, efficiency, memorability, errors and satisfaction. It is important to consider usability as it would show how an interface could support its users in achieving their goals [24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Shahida et al, have put forward an effort to identify and explore the state of the art for detecting and reporting the usability flaws and defects in usability engineering and software engineering literature [8]. Haaksma et al, have made an attempt to mark the relationship between two quality contributors to interactive applications: Usability and User Experience (UX) [9]. Raza et al, have tried to establish a relationship between usability bugs in open-source software (OSS) and online forums for public users by presenting a research model and hypothesis [10].…”
Section: Related Workmentioning
confidence: 99%
“…A definition of UX is "a person's perceptions and responses resulting from the use and/or anticipated use of a product, system or service" (International Organization for Standardization, 2010). In a study on the personal conceptions users have of usability and UX, Haaksma, De Jong, and Karreman (2018) showed that the two can best be seen as separate and complementary concepts, with usability focusing strongly on task execution and UX taking a broader perspective on the emotions associated with having and using the product. The two concepts can be used not only for technological products such as software or household appliances but also for their user support.…”
Section: Introductionmentioning
confidence: 99%